Developing a Customer Satisfaction Model for Non-Wage Recipients at BPJS Employment Office, West Kalimantan Province - Suryani, Rini; ., Zulkarnain; Alwie, Alvi Furwanti; Wijayanto, Gatot (Journal of Ecohumanism, 2024)
This study aims to develop a customer satisfaction model for BPJS Employment participants who are non-wage recipients (BPU) in West Kalimantan Province. The research focuses on the impacts of Customer Relationship Management (CRM), service quality, government role, and customer trust on participant satisfaction. Using a quantitative methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM), data from 384 respondents was analyzed. Findings indicate that CRM and service quality are significant factors in customer satisfaction, with customer trust enhancing these effects. The government’s role further moderates satisfaction, suggesting policy and regulatory support are essential for public sector service providers.